Tilapia aquaculture characterization in India: A cluster level analysis - Brako Dompreh, Eric; Bayan, Baban; Panemangalore, Arun; Rossignoli, Cristiano (2025)
Tilapia farming can play an important role in enhancing the availability and affordability of fresh fish by increasing consumption and boosting nutrition outcomes, including for the most vulnerable communities. Using structured household surveys, 2133 tilapia farmers were interviewed in three states: Kerala. Tamil Nadu and Chharttisgarh. The result of the study suggests that there are four (4) main clusters of tilapia producers in India.